(untitled) (Research, Society and Development, 2020)
This article aims to present a discussion around the history of physical education, highlighting it as an area of ​​knowledge and space for teacher training. We observed how this science, in its academic practice, went through a process of fragmentation and specialization, going beyond sports pedagogical techniques, reaching scientific knowledge about the movements of the human body. The discussions address the meanings attributed to the discipline as a science that involves body and movement. Parallel to this issue is school physical education, which does not always touch on such aspects, often summing up to games and games that keep students away from such a curricular component. In this contradictory intersection, the teacher finds it difficult to situate himself as a professional in his field of knowledge and his social function. It is a theoretical-bibliographic study, of a qualitative nature. Bibliographic research was used as a methodological resource in order to learn about the history of physical education, the genealogical construction of knowledge about the body and the integrated practice of organic and humanistic resources. The results point to the need to understand the physical education teacher’s pedagogical practice as a result of a dynamic and multifaceted process, built during his formative path and his social interactions, which will constitute his theoretical-didactic-pedagogical conceptions, which therefore requires critical reflection.